(3Yde GdGgJOG aj eYQaI Gdhba hGdGHJOGs - (3eMeO Hf eMeO Hf Ydj Hf geGe Hf GdGeGe, CHh YHO Gddg,J (B745 (3g` s
(3ChdgG (B:s
(3MOKfi GdGeGe GdaVd eMeO Hf jhSa GdZRfhi Yf Ce SdeI bGdJ cGf QShd Gddg Udi Gddg Ydjg hSde jbWY bQGAJg jbhd GdMeO ddg QH GdYGdejf Ke jba s
(3BNQgG (B:s
(3hbGd HYVge hEfi dCOYh Gddg hGdCeQ Vjb Ydi hce ef aJi VGbJ Ydjg CehQg hGdMeO ddg QH GdYGdejf Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3Ydjg bQGAI SfI (B734s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(4651) s
Keywords: (3GdbQGAGJ hGdJLhjOs